Design improvement and manufacturing of water down the hole hammer for bore drilling - Sajjad, Muhammad; Won Jung, Dong (International Journal of Engineering and Technology, 2019)
Drilling method is being used from centuries for creating holes in the field of mining and geological application. Due to this method we are able to get useful resources from earth, economically and with greater ease. Oil, gas, water and many kinds of minerals has been collected by using drilling to create boreholes in the ground. Drilling with liquid-driven down hole hammers is a new competitive method for production of boreholes. In water down-the-hole (DTH), water acts as a working fluid which transfer the energy from the piston to the hammer. There are certain parameters and by improving these we can increase the efficiency of bore drills. In our research study we are going to optimize the following, bore diameter, no of strikes and perforation speed by increasing the impact frequency of piston. The piston operates at 3102 beats per minute (51.7 Hz) which create pressure of 150 bar as a result impact energy of 1070.8 J is generated which transfer in the form of kinetic energy to the hammer. As a result of this energy output, we are able to achieve the diameter of perforation up to 1 m with penetrating speed of 1.6 m/h.Â Â